2021
DOI: 10.3389/fpls.2021.580462
|View full text |Cite
|
Sign up to set email alerts
|

Rice Seedling Growth Promotion by Biochar Varies With Genotypes and Application Dosages

Abstract: While biochar use in agriculture is widely advocated, how the effect of biochar on plant growth varies with biochar forms and crop genotypes is poorly addressed. The role of dissolvable organic matter (DOM) in plant growth has been increasingly addressed for crop production with biochar. In this study, a hydroponic culture of rice seedling growth of two cultivars was treated with bulk mass (DOM-containing), water extract (DOM only), and extracted residue (DOM-free) of maize residue biochar, at a volumetric dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 108 publications
0
15
0
Order By: Relevance
“…Plants can benefit from nanomaterials that help them absorb nutrients like N, P, and K 62 . Furthermore, the carbon nanoparticles are negatively charged and will absorb cations when put around plant roots, allowing them to adsorb and transport some of the cations required by plants 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Plants can benefit from nanomaterials that help them absorb nutrients like N, P, and K 62 . Furthermore, the carbon nanoparticles are negatively charged and will absorb cations when put around plant roots, allowing them to adsorb and transport some of the cations required by plants 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Biochar dosage could be a crucial factor in determining the biochar potential in improving plant growth [24]. Liu et al [25] observed a dose-dependent response of rice to biochar related to nutrient availability. They observed an enhancement of rice root grown under 0.05% biochar amendment, but not for 0.1% biochar.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, biochar from maize cob or straw was also capable of promoting plant growth in ryegrass fields by increasing P and K uptake in plants, without the identified action of rhizosphere bacteria ( Zhang et al, 2017 ), or in fields of soybean due to increased SOC content ( Li et al, 2020 ). Furthermore, water extracts from maize biochar could act as a bio-stimulator at a low dosage under hydroponic conditions, as low molecular weight organic acids and nanoparticles contained in the biochar can promote root growth ( Liu M. et al, 2021 ).…”
Section: Biochar From Maizementioning
confidence: 99%